Transforming warriors the ritual organization of military force - Halden, Peter; Jackson, Peter (Cass military studies, 2016)
This volume offers an inter-disciplinary study of how different cultures have sought to transform individuals into warriors. This edited volume analyses how different cultures have conceptualized the transformations of an individual passing from a peacetime to a wartime existence as an active warrior. Thus, this volume seeks to redefine theories of modernization and secularization. It shows that military organizations need to take myths, symbols and rituals seriously in order to create effective units.